Cyclometallic Zirconium Compound in Ring Opening Polymerization of L-Lactide to Biodegradable Polylactide - Haque, Ruhi; Saxena, Mohini; Shit, S.C.; Pappu, Asokan (Asian Journal of Chemistry, 2013)
Polylactide found potential as a substitute of non renewable resources. It is biodegradable and biocompatible polymer. Ring opening polymerization of polylactide has gained the importance in pharmacological, biomedical and environmental fields. In the present study, L-lactide was successfully polymerized with synthesized zirconium catalyst i.e., N-methyl benzyl amine zirconium chloride compound in bulk and in solution (THF) and the effect of monomer to catalyst ratio on the molecular weight of polymer were studied. Catalytic compound is an organometallic five membered cyclic compound, synthesized by cyclometallation process. It was observed that cyclometallic zirconium compound can effectively polymerize L-lactide to high molecular weight polylactide. Cyclometallic compound and polylactide was characterized by FT-IR, 1H and 13C NMR, CHNS techniques. Molecular weight was determined by GPC and thermal study was done by TGA-DSC. Surface morphology and shape was evaluated via FESEM.